An analysis of factors affecting student wellbeing: Emotional intelligence, family and school environment - Ahmad Muhibbin; Patmisari Patmisari; Noor Banu Mahadir Naidu; Wibowo Heru Prasetiyo; Muhammad Luthfi Hidayat (Institute of Advanced Engineering and Science, 2023)
This research aims to identify the role of family and school environments in predicting emotional intelligence and student well-being. It also examines whether or not emotional intelligence acts as a mediator. A total of 500 senior high school students from 16 private high schools in Pemalang District, Indonesia, completed this survey in the 2020-2021 academic year. Data analysis was carried out using Structural Equation Modeling (SEM) analysis with Partial Least Square (SEM-PLS). The results show that family environment affects the fulfilment of student well-being. Emotional intelligence was not an essential mediator in the relationship between the family environment and student well-being. The school environment also had a decisive role in fulfilling student well-being. Emotional intelligence was an essential mediator between the school environment and student well-being. Student well-being should be realized. It is necessary to address the welfare of teachers in the school environment and the awareness of parents in the family to assist students. Teachers’ and students’ interests are closely related. When the welfare of teachers is prioritized, it will improve harmonious relationships in the school environment. Likewise, when parents accompany their children at home, the children will feel more prosperous.